Bridge Vibration Monitoring Using ESP32 and MPU6050: Pemantauan Getaran Jembatan Menggunakan ESP32 dan MPU6050 - Muhadzdzib Sayyidul Quthb; Arief Wisaksono (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Structural health monitoring is essential for maintaining bridge safety and supporting infrastructure management through continuous observation of operational conditions. Specific Background: Bridge vibrations generated by passing vehicles can contribute to structural degradation, creating a need for real-time monitoring systems that allow remote data access and storage. Knowledge Gap: Existing studies have demonstrated vibration measurement and bridge monitoring approaches; however, a practical system integrating vibration sensing, wireless communication, and cloud-based data recording through a simple spreadsheet platform remains limited. Aims: This study aimed to develop a bridge vibration monitoring system using an ESP32 microcontroller, an MPU6050 accelerometer and gyroscope sensor, and Google Sheets as a remote monitoring and database platform. Results: The developed system successfully detected, transmitted, stored, and displayed bridge vibration data in real time through an internet connection. Measured vibration values were classified according to vehicle type, with recorded vibration speeds of 1.87 m/s for tronton trucks, 1.47 m/s for trucks, 0.40–0.97 m/s for buses, and 0.11–0.39 m/s for cars. Novelty: The proposed system combines ESP32-based wireless sensing, MPU6050 vibration measurement, and direct Google Sheets integration within a single monitoring framework for bridge vibration observation. Implications: The system provides a practical approach for remote bridge condition monitoring and data archiving, supporting routine observation and future assessment of bridge structural conditions.Highlights: Real-time vibration data were transmitted and stored through an online spreadsheet platform. Vehicle categories produced distinct measured vibration ranges on the observed structure. Wireless sensing architecture enabled remote observation and database recording. Keywords: Bridge Vibration Monitoring; Structural Health Monitoring; ESP32; MPU6050; Internet of Things